(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The structural transition toward a digital knowledge economy dictates an urgent paradigm shift in tertiary learning environments, moving from traditional e-learning to adaptive, intelligent academic ecosystems. This study critically investigates the dual requirements—pedagogical and technological—necessary for the effective implementation of SMART Education within higher educational institutions. Utilizing a mixed-methods empirical framework involving 450 undergraduate students and 65 faculty members at the Tashkent State Pedagogical University, the research evaluates the symbiotic integration of Artificial Intelligence (AI) analytics, Internet of Things (IoT) infrastructure, and advanced didactic methodologies. Empirical data obtained within the research framework demonstrate that merely deploying advanced hardware without parallel pedagogical restructuring yields negligible academic improvements. Conversely, synchronizing intelligent Learning Management Systems (LMS) with active pedagogical strategies—such as personalized learning tracks and real-time cognitive feedback—resulted in a 28.4% increase in student knowledge retention and a significant optimization of independent learning hours. The dynamics of the observed outcomes indicate that SMART Education is fundamentally not a mere technological upgrade, but a profound didactic transformation. Establishing a highly efficient SMART university requires a strict institutional equilibrium between capital investment in digital infrastructure and the continuous, targeted elevation of digital-pedagogical competencies among academic staff.